Hadith #2888 - Sunan Abi Dawud - Abu Bakr bin Abi Uvais أبو بكر بن أبي أويس; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; al-Bara' bin Azib bin al-Harith; Mansur bin Abi Mazahim (Sunan Abi Dawud)
The last verse revealed about the decease who left no descendants or ascendants: “They ask thee for the legal decision. Say: Allah directs (thus) about those who leave no descendants or ascendants as heirs.”
Grade: Sahih